Synthesis and Rh(I)‐catalyzed polymerization of 1,3‐diphenylyne–calix[4]arene compounds: novel conjugated, calixarene‐based polymers - Costa, Alexandra I. (2020)
The synthesis of two 1,3‐bis(4‐ethynylbenzyloxy)calix[4]arenes, 5,11,17,23‐tetrakis(1,1‐dimethylethyl)‐25,27‐bis(4‐ethynylbenzyloxy)‐26,28‐dihydroxycalix[4]arene (1 ) and 25,27‐bis(4‐ethynylbenzyloxy)‐26,28‐dihydroxycalix[4]arene (2 ), was accomplished through Sonogashira coupling of appropriate calixarene derivatives. Methods for the polymerization of these bifunctional building blocks with Rh(I) as a catalyst, leading ultimately to conjugated polymers having calix[4]arene units incorporated into the main chain, were explored. Calixarenes 1 and 2 were efficiently polymerized with rhodium‐based initiators and afforded the conjugated polymers poly{5,11,17,23‐tetrakis(1,1‐dimethylethyl)‐25,27‐bis(4‐ethynylbenzyloxy)‐26,28‐dihydroxycalix[4]arene} (poly 1 ) and poly{25,27‐bis(4‐ethynylbenzyloxy)‐26,28‐dihydroxycalix[4]arene}. Depending on the conditions, high conversions and good yields were obtained. The effects of adding cocatalysts (NHEt2 and/or PPh3) were studied in connection with the number‐average molecular weight and the molecular weight distribution of the resultant polymer (poly 1 ) and tentatively correlated with the formation of low‐molecular‐weight materials. A catalytic system containing triphenylphosphine as the sole additive ([Rh(nbd)Cl]2; [Rh]/[PPh3] = 0.5) proved to be the best for the polymerization of p ‐tert ‐butylcalixarene compound 1 . Linear polymers having high number‐average molecular weights (up to 1.1 × 105 g mol−1) with low polydispersities were produced under these conditions. For debutylated homologue 2 , its polymerization was best carried out in the absence of any added cocatalyst. A cyclopolymerization route, comprising the intramolecular ring closing of the calix[4]arene pendant ethynyl groups followed by an intermolecular propagation step, is advanced to explain the results.